ONLINE PURCHASE INTENTION MODEL: A NEW BREAKTHROUGH IN MARKETING STRATEGIES - Jamal, Fauziyah Nur; Rahmiati, Filda; Solihudin, Ahmad Rizal; Gumelar, Bagus; Rahmi, Mustika; Pangestu, Rangga Alfaro; Wibowo, Indi Deli (Proceeding of the International Conference on Family Business and Entrepreneurship, 2024)
Purchase decisions are fundamentally the most important aspect for consumers when making purchases. Consequently, consumers often feel confused and carefully consider many factors during the purchasing process. In this context, Shopee needs several supporting factors that can influence purchase decisions. This study aims to determine the influence of security, ease of use, and online consumer reviews on online purchase decisions on the Shopee application. The sample in this study consists of 90 respondents who are users of the Shopee application in the Special Region of Yogyakarta. The sampling technique used is non-probability sampling with a quantitative approach and uses the SEM-PLS program for data analysis. The results of this study indicate that security has a positive and significant influence on online purchase decisions on the Shopee application. Ease of use has a positive and significant influence on online purchase decisions on the Shopee application. Online consumer reviews do not have a significant influence on online purchase decisions on the Shopee application. It can be used to improve marketing performance as an effective marketing strategy for online shop providers. This research is expected to contribute to the development of knowledge and provide companies with an effective marketing strategy.